Tinjauan Yuridis Tindak Pidana Penggelapan Sertifikat Hak Milik Studi Kasus Putusan Nomor 733/Pid.B/2018/Pn.Dps. - Made Fiorentina Yana Putri; I Made Minggu Widyantara; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
The crime of embezzlement is a form of crime against human assets, which is regulated in the Criminal Code. The crime of embezzlement often occurs in all fields, even the perpetrators at various levels of society, from the lowest level to the top layer, can commit the crime of embezzlement, which is a crime that starts with a belief in other people so that trust disappears because of the weakness of honesty. This study aims to examine the legal arrangements for embezzlement and to analyze the legal considerations in imposing a verdict on the embezzler of title deeds that may result in losses. The method used was normative legal research with the statutory, case, and conceptual approaches. Sources of data were sourced from primary and secondary legal materials obtained through interviews and documentation and recording. The results showed that in case No.733 / Pid.B / 2018 / PNDPS, it was found that it had fulfilled the elements in article 372 because it fulfilled the elements of embezzlement, the perpetrator was subject to sanctions, the perpetrator was charged with article 372 of the Criminal Code where the threat of punishment is a maximum of four years in prison and a maximum fine of nine hundred rupiahs. The legal considerations by the judge in making the verdict in case No.733 / Pid.B / 2018 / PNDPS were in accordance with existing legal regulations, based on evidence, namely, witness testimony and the defendant's testimony during the trial. The Panel of Judges is expected to be based on the facts revealed during the trial and to judge that the defendant can be held accountable for his actions, that the defendant carried out his actions in a condition that was both mentally and physically healthy